2018
DOI: 10.1021/acsami.7b19204
|View full text |Cite|
|
Sign up to set email alerts
|

Biomimetic Silk Scaffolds with an Amorphous Structure for Soft Tissue Engineering

Abstract: Fine tuning physical cues of silk fibroin (SF) biomaterials to match specific requirements for different soft tissues would be advantageous. Here, amorphous SF nanofibers were used to fabricate scaffolds with better hierarchical extracellular matrix (ECM) mimetic microstructures than previous silk scaffolds. Kinetic control was introduced into the scaffold forming process, resulting in the direct production of water-stable scaffolds with tunable secondary structures and thus mechanical properties. These biomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
107
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(113 citation statements)
references
References 68 publications
6
107
0
Order By: Relevance
“…Different conformations of silk fibroin usually show various degradation peaks, where the random coil is degraded at the lowest temperature while silk II is impacted at the highest temperature. (Dong et al, ; Sang et al, ) The MS scaffolds showed a degradation peak at 274°C while two degradation peaks at lower temperatures (254°C and 267°C) appeared in the curves of the TS scaffolds, confirming the increased amorphous state of the TS scaffolds (vs. the MS). The crystallization peak at 200–220°C usually appears in the curves of amorphous RSF scaffolds, but disappeared in the curves of the TS scaffolds, which revealed their higher stability.…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…Different conformations of silk fibroin usually show various degradation peaks, where the random coil is degraded at the lowest temperature while silk II is impacted at the highest temperature. (Dong et al, ; Sang et al, ) The MS scaffolds showed a degradation peak at 274°C while two degradation peaks at lower temperatures (254°C and 267°C) appeared in the curves of the TS scaffolds, confirming the increased amorphous state of the TS scaffolds (vs. the MS). The crystallization peak at 200–220°C usually appears in the curves of amorphous RSF scaffolds, but disappeared in the curves of the TS scaffolds, which revealed their higher stability.…”
Section: Resultsmentioning
confidence: 88%
“…Silk fibroin conformations of the scaffolds were evaluated by FTIR. The amide I peaks of silk fibroin are usually used for the analysis of different secondary conformations where the peaks at 1610–1630 cm −1 are characteristic of beta‐sheet conformation while the peaks at 1635–1655 cm −1 are attributed to amorphous states (Bai et al, ; Sang et al, ; Wang et al, ). As shown in Figure a, typical peaks of amorphous structures and beta‐sheet conformations appeared on FTIR curves of the TS and MS scaffolds, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations